Sistem Informasi Perjalanan Dinas Berbasis Elektronik Pada Dinas Pertanian Kabupaten Pati - Salahuddin, Ahmad Fikri; Meimaharani, Rizky Sari; Nurkamid, Mukhamad (STIKOM Tunas Bangsa Pematangsiantar, 2022)
The development of technology, especially computers at this time has a very important role in life in society. Technology that develops according to the demands of the times is expected to be a supporting tool to deal with problems that arise in managing and solving problems in the company or organization. Similarly, the Office of The Agriculture Office of Pati Regency is expected to provide accurate and accurate information in making a travel warrant. Pati District Agriculture Office does not currently have an application to make a letter, the office is currently making letters still manually. This Information System is designed using the PHP programming language. This Information System is designed in such a way as to facilitate the creation of faster and more accurate and complete letters. This Information System is important because it makes it easier to create a travel warrant because it can shorten the time.